Macrophage-related inflammatory responses to degradation products of biodegradable molybdenum implants - Danyang Liu; Jiahao Chen; Jiannan Zhou; Jingtao Dai; Haotian Qin; Guojiang Wan; Junyu Qian; Ping Li; Jiang Li (Materials Today Bio)
Metallic molybdenum (Mo) has been increasingly recognized as a potential biodegradable metal for biomedical implants. However, the macrophage-mediated inflammatory responses to Mo-based implants remain underexplored. This study examined the in vitro inflammatory reactions of macrophages to the degradation products of biodegradable Mo implants. The short-term and long-term biodegradation behavior and the subsequent impact on cytotoxicity, metabolism, and macrophage polarization were assessed. Both Mo and its degradation products were shown to be non-toxic within macrophage tolerance limits. Nevertheless, morphological changes and pro-inflammatory polarization were observed in cells around Mo-based specimen. Notably, matrix metalloproteinase 9 (Mmp9) was identified as a key gene influencing macrophage polarization in proximity to Mo. Additionally, pre-treating the Mo specimens in culture medium for 24 h significantly mitigated its stimulatory effects on cells. These results demonstrated the significance of optimizing Mo pre-treatment methods to prevent localized inflammation associated with its degradation. Specifically, pre-treatment of Mo can effectively mitigate the adverse impacts of its early degradation on macrophages and the surrounding immune environment. Our research into these early degradation phases introduces new avenues for studying molybdenum's immunomodulatory properties, potentially through precise control of its release and the targeted expression of pivotal genes.